Examining Productivity Skills and Academic Stress among High School Students at Ipil Montessori Academy in the Philippines - Magallanes, Sarah Jane; Perater, Ruben; Magdua, Rosejane; Orditor, Clonny Liza; Macrohon, Jomer; Surtida, Ronalyn; Deniega, Dayrylle May; Engaling, Kassie; Ariola, Mary Frietz; Cagurin, Danica (Paedagogia: Jurnal Pendidikan, 2025)
This study investigated the relationship between productivity skills, with a focus on time management, and academic stress among high school students at Ipil Montessori Academy. Specifically, it aimed to determine the level of productivity skills among students, examine whether productivity skills differ by gender, and explore the association between productivity skills and academic stress. A quantitative correlational design was employed, involving 100 randomly selected participants from junior and senior high school levels, consisting of 61 females and 39 males, with ages ranging from 12 to 17 years. Data were collected using two standardized instruments, the Time Management Inventory and the Academic Stress Inventory, both of which demonstrated high internal consistency. Descriptive analysis revealed that students exhibited moderate productivity skills overall, with neutral attitudes toward time and moderate ability in time planning and managing time-consuming activities. Analysis of gender differences indicated no significant variations in productivity skills or academic stress levels, showing that both male and female students adopt similar approaches. The results further showed that academic stress among respondents was generally at an indifferent level, with group study stress emerging as the highest source of stress and teacher-related stress as the lowest. Correlational analysis indicated no significant relationship between productivity skills and academic stress. These findings suggest that while students demonstrate moderate productivity and neutral stress levels, productivity skills alone are insufficient to explain academic stress, highlighting the need to consider additional personal and contextual factors.